Introduction to Programming using Ozobots in an Economics Major CS-Class - Müller-Unterweger, Michaela; Berges, Marc-Pascal (WiPSCE '24: Proceedings of the 19th WiPSCE Conference on Primary and Secondary Computing Education Research, 2024)
Introducing programming to non-majors is challenging.To increase accessibility, Ozobots are integrated into an introductory programming class for grammar schools focusing on economic topics (Economics major).Besides a description of how to integrate the tool, a comparison of students' learning outcomes exposed to Ozobot-assisted instruction with those using traditional programming tools is described.Therefore, three classes were assessed with a pre-/posttest on basic algorithmic competencies.The results highlight the potential of robotics in programming education and emphasize the importance of hands-on, experiential learning for fostering a deeper understanding of algorithmic design and programming concepts.
CRIS-Team Scopus Importer:2024-10-18
Keywords: algorithm; business administration; computer science; Ozobot